2010
DOI: 10.1016/j.ijantimicag.2009.10.020
|View full text |Cite
|
Sign up to set email alerts
|

In vitro interference of β-lactams with biofilm development by prevalent community respiratory tract isolates

Abstract: Interference of cefditoren (CDN) and amoxicillin/clavulanic acid (AMC) with biofilm production was studied using 11 Streptococcus pneumoniae isolates with minimum inhibitory concentrations (MICs) ranging from 0.015 g/mL to 0.5 g/mL for CDN and from 0.06 g/mL to 2 g/mL for AMC (except for one isolate with an AMC MIC of 8 g/mL) and 5 Haemophilus influenzae isolates with MICs of 0.03-0.06 g/mL for CDN and 0.5-16 g/mL for AMC. Slime production was assessed in antibiotic-free medium and with 0.03 g/mL CDN o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
4
0
2
Order By: Relevance
“…The isolates were evaluated in replicates of five. The percent reduction from the control was calculated for biofilm biomass and compared between isolates using the formula {([untreated control Ϫ treatment]/untreated control)} ϫ 100 (36). This formula calculates the percent reduction in biofilm biomass for each treatment, with a value of 0% indicating no change from the untreated controls, a value of 100% indicating no reduction from the control (no biofilm biomass measured), and a negative value indicating an increase in biofilm biomass following treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The isolates were evaluated in replicates of five. The percent reduction from the control was calculated for biofilm biomass and compared between isolates using the formula {([untreated control Ϫ treatment]/untreated control)} ϫ 100 (36). This formula calculates the percent reduction in biofilm biomass for each treatment, with a value of 0% indicating no change from the untreated controls, a value of 100% indicating no reduction from the control (no biofilm biomass measured), and a negative value indicating an increase in biofilm biomass following treatment.…”
Section: Methodsmentioning
confidence: 99%
“…However, it has been reported that amoxicillin, erythromycin and levofloxacin at supra‐MIC concentrations are less active against biofilm‐associated pneumococci than against planktonic cells (del Prado et al ., 2010), and it has been suggested that isolates forming biofilms from patients with cystic fibrosis may have become highly adapted to the presence of antibiotics such as penicillin and tetracycline (García‐Castillo et al ., 2007). In addition, cefditoren, an oral third‐generation cephalosporin, better interferes with S. pneumoniae biofilm development than does amoxicillin‐clavulanic acid (Maestre et al ., 2010). Interestingly, moxifloxacin, a fourth‐generation oral fluoroquinolone, can inhibit the formation of, and indeed disrupt, biofilms produced by respiratory pathogens, including S. pneumoniae , at concentrations easily achieved in the bronchial mucosa (Roveta et al ., 2007).…”
Section: Prevention Of Biofilm Formation and Therapymentioning
confidence: 99%
“…Additionally, the use of antibiotics may also reduce inflammatory parameters [ 107 ]. Cefditoren showed to interfere biofilm formation in a study comparing cefditoren (0.03 mg/l) with amoxicillin/clavulanic acid (1/0.5 mg/l) that concluded that both compounds were able to reduce biofilm formation by the 10 pneumococcal isolates tested, with significant higher reductions in the case of cefditoren [ 126 ]. With respect to inflammation, one study comparing cefditoren and levofloxacin found that the use of both antimicrobials was associated with significant reductions of IL-6 and KL-6, two mediators of lung inflammation and epithelial damage [ 107 , 127 ].…”
Section: From Pk/pd Interpretation To Clinical Data In Adultsmentioning
confidence: 99%